Migration and financial well-being: the impact of acculturation and financial socialization with mediating role of financial behavior - Susilowati, Diyah; Mukhlis, Imam; Andayani, Endang Sri; Kartiwi, Mira (2023)
The dilemma of the large population of Indonesia being disproportionate to the number of jobs available in the country has resulted in international migration to achieve household financial well-being, and most immigrants 55% migrate to Malaysia (World Bank, 2017). This study aims to measure whether acculturation and financial socialization influence financial well-being mediated by financial behavior among Indonesian immigrant housewives from South Sulawesi in Sabah, Malaysia. This research uses the Partial Least Square path modeling technique, and 384 respondents showed that acculturation and financial socialization significantly affected financial behavior. Financial behavior has a significant impact on financial well-being. In addition, financial behavior significantly mediates acculturation, financial socialization, and financial well-being. The results of this research can help the government and palm oil plantations to create policies and possible intervention programs to help Indonesian immigrants manage their financial behavior in order to achieve financial well-being through financial literacy programs, holding outreach to their workers to be careful in managing finances such as not getting caught up in online lending practices that are currently widespread, reducing consumptive shopping behavior non-essential, and facilitate pension programs not only for Malaysian citizens but also Indonesian citizens.